Kebijakan Pengelolaan Sumber Daya Alam Bagi Pembangunan Berkelanjutan Berwawasan Lingkungan - Yasminingrum, Yasminingrum (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
Natural resource management policies are not carried out by exploiting natural resources. irrationally which will result in the destruction of natural resources, a damaged living environment, on the contrary, policies in managing natural resources are directed at maintaining their sustainability which will realize sustainable development with an environmental perspective that can be utilized. for present and future generations. Fostering long-term development concludes a just, prosperous society based on Pancasila which contains the characteristics of human relations with society and humans with their environment.